Réponses

  • Utilisateur Brainly
2013-01-22T18:36:11+01:00

Alors tu n'as pas fait les 4 produits, mais seulement les 2 premiers :

 

(2+√5) (3√5-4)=2*(3√5-4)+√5 (3√5-4)=6√5-8+15-4√5=2√5+7

Meilleure réponse !
2013-01-22T18:48:14+01:00

Coucou,

 

Développons (2+√5) (3√5-4)

2 x (3√5) + 2 x (-4) + √5 x (3√5)  + √5 x -4

=(2 x 3)√5  - 8 + 3 x (√5 x √5) - 4√5       3 x √5 x √5 = 3 x 5  (car √5 x √5 = 5) = 15

=6√5  - 8 + 15  - 4√5  

=6√5 +  7 - 4√5

=7 + 6√5 - 4√5            on multplie 6 et 4 par la même chose, par √5

=7 + (6 - 4)√5   

=7 + 2√5

 

Voilà ;)